The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/spq0000173
|View full text |Cite
|
Sign up to set email alerts
|

The role of colorism in explaining African American females’ suspension risk.

Abstract: African American female students' elevated suspension risk has received national attention. Despite a number of studies documenting racial/ethnic disparities in African American females' school suspension risk, few investigations have attempted to explain why these disparities occur. The purpose of this study was to examine the role of colorism in explaining suspension risk using a nationally representative sample of adolescent females. Controlling for individual- and school-level characteristics associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…Such mistreatment and marginalization not only engendered emotional and psychological trauma, but were especially impactful during adolescence. Similar to other ethnic groups, African American girls can experience negative social and psychological outcomes as a result of colorist practices and perceptions (Blake et al, 2017; Hunter, 2005; Keith & Herring, 1991; Landor et al, 2013; Wilder, 2010). An expanding body of literature has found that colorism can negatively affect psychological well-being (J.…”
mentioning
confidence: 99%
“…Such mistreatment and marginalization not only engendered emotional and psychological trauma, but were especially impactful during adolescence. Similar to other ethnic groups, African American girls can experience negative social and psychological outcomes as a result of colorist practices and perceptions (Blake et al, 2017; Hunter, 2005; Keith & Herring, 1991; Landor et al, 2013; Wilder, 2010). An expanding body of literature has found that colorism can negatively affect psychological well-being (J.…”
mentioning
confidence: 99%
“…Age, grade, and race/ethnicity (White, Black or African American, Hispanic or Latino/a, other) were reported by participants as part of the school-based survey. Parents’ education level at Wave I was used as a proxy for SES given that parent education is highly associated with income over time and is often a stable measure of SES (Blake et al, 2017; Sirin, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Through processes of social comparison, youths may formulate ideas about the meaning of their skin tone in relation to their peers. For instance, the disparate treatment of black Americans with darker skin tone in terms of teacher engagement as well as punishment (Blake et al 2016; Tatum 2004) may signal to adolescents that having darker skin tone is a stigmatized status. Thus, youths may develop ideas about skin tone by observing how their peers are treated both by adults and by other peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings from this work suggest that the impact of skin tone on both depression and self-rated mental health operate, in part, through increased exposure to discrimination among black Americans with darker skin tone (Monk 2015). Importantly, this body of work highlights the way in which skin tone functions as a key system of stratification within the black population (Blake et al 2016; Hunter 2013; Monk 2014, 2015). Although the skin tone–health relationship has been demonstrated in several studies using data from adult populations (Cobb et al 2016; Monk 2015; Perreira and Telles 2014), scholars have yet to determine whether these skin tone differentials in discrimination and mental health emerge before adulthood.…”
Section: Introductionmentioning
confidence: 98%